The development risks in the digital era - Izquierdo Grau, Guillem (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
One of the pillars on which product liability law is based is the exemption of the producer from liability for development risks. According to this exemption from liability, the producer is not liable for the damage caused to the injured party if, at the time the product was put into circulation, the state of scientific and technical knowledge did not allow the existence of the defect to be discovered. The Proposal for a Directive drafted by the European Commission and published on 28 September 2022 continues to provide in article 10.1.e) for exoneration from liability for development risks. The Proposal for a Directive refers recital no. 39 to this particular issue, which introduces some requirements for the assessment of such a cause for exoneration from liability. However, despite this recognition, does this cause of exoneration from producer liability fit into the digital paradigm, and how can it be applied to damage caused by defects in products with digital elements that incorporate artificial intelligence?